Adherence to antiretroviral medications and quality of life among people living with HIV/AIDS in Chikankata,Livingstone and Mwinilunga districts in Zambia - Kalembela, Valerie M.; Libingi, Muleya Linda; Yung'ana, Mbambo Musole; Zulu, Debonair (Lusaka: University of Zambia , School of Medicine, 2013)
The purpose of this study was to determine the relationship between adherence to antiretroviral medications and quality of life among people living with HIV/AIDS in urban and rural zambia. The study was cross-sectional and descriptive. It was conducted in October 2012 from four sites namely Lusaka, Livingstone, Chikankata and Mwinilunga districts ART clinics respectively. It involved 200 simple randomly selected selected HIV-positive clients, fifty from each site.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: HIV infections; HIV Infections--drug therapy; Patient compliance